DIGITAL LEADERSHIP: DESIGNING A COMMUNICATIONS-CENTERED IT GOVERNANCE FRAMEWORK FOR ORGANIZATIONS - Harjono Padmono Putro (Sean Institute, 2023)
Organizations need to reinvent strategies to face rapid changes in the digital era. A key challenge for companies is how they can take advantage of the opportunities emerging from this digital disruption by accelerating the company's digital transformation, which should be led by digital leadership capabilities. This research aims to analyze and design an IT governance framework that focuses on communication as a critical element in supporting effective digital leadership. This research uses a qualitative approach with descriptive methods. The research results highlight the importance of digital leadership and the integration of communication-centered IT governance in facing the challenges of digital transformation. Research shows that digital leaders need to articulate a vision focused on leveraging technology to improve the effectiveness and efficiency of organizational communications. Forming cross-departmental teams or committees is key to integrating efforts between IT and communications. In addition, IT policy designs that cover communication aspects need to pay attention to security standards and data governance, in accordance with the organization's communication values. Policy dissemination and regular training are essential to ensure the necessary understanding and skills across the organization. Regular evaluation of the implementation of the IT governance framework shows that adaptability and responsiveness to changes in the organization and the external environment are the keys to long-term success.